2019
DOI: 10.1038/s42005-019-0208-7
|View full text |Cite
|
Sign up to set email alerts
|

High-accuracy bulk electronic bandmapping with eliminated diffraction effects using hard X-ray photoelectron momentum microscopy

Abstract: A key benefit of angle-resolved photoelectron spectroscopy (ARPES) in the X-ray range is the significant increase of the information depth, thanks to the large inelastic mean-free-path of the escaping photoelectrons. In practice hard X-ray ARPES (HARPES) faces severe challenges by low cross sections, large photon momentum transfer, and in particular strong phonon scattering and photoelectron diffraction effects. Here, we show that these challenges can be overcome by extending ultra-efficient time-of-flight mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…This suggests possible applications of hXPD for element-resolved strain analysis in materials [50,51]. Valence-band patterns are recorded at identical setting of the microscope [47] thus opening the path to a one-to-one correspondence of changes in the geometric and electronic structures, measured quasi simultaneously. Static and dynamic strain manipulation is emerging as a new avenue to tune and shape a material's electronic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests possible applications of hXPD for element-resolved strain analysis in materials [50,51]. Valence-band patterns are recorded at identical setting of the microscope [47] thus opening the path to a one-to-one correspondence of changes in the geometric and electronic structures, measured quasi simultaneously. Static and dynamic strain manipulation is emerging as a new avenue to tune and shape a material's electronic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements for tungsten yielded m eff /m e =1.07 at 1 keV [38] and 1 at 6 keV [46]. For Mo we found m eff /m e =1.03 at 460 eV and m eff /m e =1 already at 1.7 keV [47]. For these reasons, the panels list the final-state energies and not the photon energies.…”
Section: Carbon 1s Diffractogramsmentioning
confidence: 94%
“…Therefore, despite the low photoexcitation cross sections at high photon energies also momentum microscopy in the HAX-PES regime should be feasible. This was demonstrated very recently using a time-of-flight spectrometer [41].…”
Section: Haxpes Spectromicroscopymentioning
confidence: 91%
“…In order to overcome the intensity/resolution problem of photoelectron spectroscopy in the X‐ray range, we have developed a conceptually new approach, termed time‐of‐flight (ToF) momentum microscopy. Based on work at low energies we extended the method at first to the soft X‐ray range and in summer 2018 to the hard X‐ray range employing a special high‐energy optics . In contrast to conventional electron analyzers that are working in terms of angular coordinates, these photoelectron microscopes directly measure the (lateral) k x ‐ and k y ‐coordinates in a large range of up to 20 Å −1 diameter.…”
Section: The Methodsmentioning
confidence: 99%
“…Panel (f) shows the corresponding spectrum, the narrow peak labeled hν originates from scattered photons and gives a marker for time‐zero. Previous work has shown that there is a significant XPD contribution in the valence‐band patterns. In order to eliminate this effect, the raw data have been corrected using a C 1s diffraction pattern taken at the same kinetic energy as the valence pattern.…”
Section: Photoelectron Momentum Microscopymentioning
confidence: 99%